PENERAPAN TEKNOLOGI FISH CALLER LACUBA (LAMPU CELUP BAWAH AIR) PADA MASYARAKAT NELAYAN DI DESA CILELLANG KABUPATEN BARRU - Awalia, Nurul; Lamada, Mustari (Jurnal Pendidikan Teknologi Pertanian, 2018)
Based on the data obtained, in reality not a few fishermen find it difficult to catch fish. In addition, the lack of their catch is the main impact of the above problems. If this happens continuously then the number of traditional fishermen will decline so that the need for a concept and tools that can help in increasing the catch one of them is the application of technology LACUBA. The purpose of this research is to apply LACUBA technology (Lampu Kecup under water) which can help the income of fisherman community and to know the fisherman's response to LACUBA technology (Water dye underwater lamp) specially on coastal community Cilelang, Kab. Barru. Implementation of this activity is in the village of Cilellang Kab. Barru in May 2018. This research instrument uses LACUBA (Dye underwater light) which is the result of a series of some electronic components such as Aki (Accu), Dimmer Series and Inverter Circuits. From the calculation of the results of the analysis of fishermen's income data in the village of Cilellang, Kab. Barru before and after the use of LACUBA (Submersible underwater lights) changes significantly. From the data obtained shows that before the use of LACUBA Technology, Fishermen Society only get the catch of an average of 21.88 Kg / day. Meanwhile, after the use of LACUBA technology, the average of the acquisition increased to 43.78 kg / day. Based on the results of this study it can be concluded that there is a significant influence on the use of technology LACUBA (Water dye underwater light) to the fishing results in the village of Cilelang Kab. Barru